Clinical relevance of positive human parechovirus type 1 and 3 PCR in stool samples. (20th February 2014) - Wildenbeest, J. G.; Benschop, K. S. M.; Minnaar, R. P.; Jongh, S. Bouma‐de; Wolthers, K. C.; Pajkrt, D.; Zupanc, A.
Abstract Human parechoviruses (HPeV) cause symptoms ranging from severe neonatal infections to mild gastrointestinal and respiratory disease. Use of PCR and genotyping has markedly improved the detection rate of HPeV but has simultaneously raised questions about the clinical relevance of positive tests. This retrospective study correlates positive HPeV1 or HPeV3 PCR tests in stools from children with their symptoms to determine clinical relevance. Children with HPeV1‐ or HPeV3‐positive stool samples, as detected by real time RT‐PCR and direct genotyping, between 2004 and 2008 were selected. Clinical data were retrospectively collected from the patient's files and results were compared. One hundred and thirty‐eight children with positive HPeV1 (n = 112) or HPeV3 (n = 26) stool samples were identified. Significantly more HPeV3‐infected children were neonates or infants younger than 6 months of age. Meningitis or sepsis‐like illnesses were diagnosed most frequently and were found in significantly younger children. Almost half of HPeV1‐infected children had an underlying disease. Mild gastrointestinal disease was seen most frequently in these children. There was no clear correlation between viral load (Ct value) and severity of symptoms. In conclusion, HPeV3 detected by PCR in stool samples is associated with clinically relevant disease. For HPeV1, a positive stool sample is mainly associated with symptoms in children with underlying disease.